ANALISIS PENGARUH KUALITAS PELAYANAN, PENETAPAN HARGA DAN FASILITAS TERHADAP KEPUASAN PASIEN - Suyitno Suyitno (Politeknik Negeri Batam, 2018)
ABSTRACT A government institution engaged in service delivery, especially health services, consumer satisfaction a benchmark of the success of the institution. As more and more customers are satisfied with the services of an institution, more and more consumer visits to use the services of the service provider can ultimately increase the revenue of the company. This study analyzed the effect of service quality variables, price and facility determination on patient satisfaction at Malang District General Hospital. The questionnaires were filled by 86 patients who came to the Malang District General Hospital, and the data were processed using multiple linear regression using SPSS version 11.5 software. The result showed that service quality, price and facility have significant effect either partially or simultaneously on patient satisfaction. Besides, the results of this study indicate that service quality has a dominant influence on patient satisfaction in Malang District General Hospital.